Extended Prophylactic Antibiotics for Mastectomy with Immediate Breast Reconstruction: A Meta-analysis - Hai, Yang (Plast Reconstr Surg Glob Open, 2020)
BACKGROUND: The risk of surgical site infection (SSI) for breast surgery in patients without additional risk factors is low, below 5%. Evidence shows the risk of SSI is significantly elevated in patients undergoing immediate breast reconstruction (IBR). However, there is no consensus regarding the use of extended antibiotic prophylaxis. We aim to determine the effect of extended antibiotic prophylaxis on the incidence of SSI after IBR. METHODS: PubMed and Scopus were searched by 2 independent reviewers. Data abstracted included types of study, basic characteristics, detailed antibiotic prophylaxis information, SSI event, and other secondary outcomes. We calculated the risk ratio (RR) and 95% confidence interval (CI) for each study and used a random-effects model to estimate the results. Study quality, bias, and heterogeneity were also analyzed. RESULTS: A total of 11 studies (15,966 mastectomy procedures) were included. We found an overall 5.99% SSI rate in our population. Three studies comparing topical antibiotics with no topical antibiotics demonstrated statistical significance (RR = 0.26, 95% CI: 0.12–0.60, P = 0.001), whereas 8 studies comparing extended systemic antibiotics with standard of care found no statistical significance (RR = 0.80, 95% CI: 0.60–1.08, P = 0.13). CONCLUSIONS: In the setting of IBR following mastectomy, there is insufficient evidence for the use of extended prophylactic antibiotics to reduce SSI rates. Well-designed randomized controlled trials in patients undergoing IBR should be conducted to determine the appropriate regimen and/or duration of prophylactic antibiotics on SSI outcomes.